Screening of Novel Pharmacogenetic Candidates for Mercaptopurine-Induced Toxicity in Patients With Acute Lymphoblastic Leukemia - Minyuan Cao; Minyuan Cao; Dandan Yin; Yun Qin; Fei Liao; Yali Su; Xuyang Xia; Ju Gao; Yiping Zhu; Wei Zhang; Yang Shu; Xiaoxi Lu (Frontiers Media S.A., 2020)
A small proportion of patients with acute lymphoblastic leukemia (ALL) may experience severe leukopenia after treating with 6-mercaptopurine (6MP), which can be largely explained by germline variants in TPMT and NUDT15. However, a minority of patients who suffered such adverse drug reaction have NUDT15wt/wtTPMTwt/wt genotype, indicating that other genetic factors may take part in. In this study, we genotyped 539 exon-located nonsilent pharmacogenetic variants in genes involved in phase I/II of drug metabolism in 173 pediatric patients with ALL and conducted association screening for 6MP-induced leukopenia. Besides NUDT15 (rs116855232, P = 6.4 × 10−11) and TPMT (rs1142345, P = 0.003), a novel variant was identified in CYP2A7 gene (i.e., rs73032311, P = 0.0007), which is independent of NUDT15/TPMT variant. In addition, a variant (i.e., rs4680) in COMT is significantly associated with 6MP-induced hepatotoxicity (P = 0.007). In conclusion, variants in CYP2A7 and COMT may be considered as novel potential pharmacogenetic markers for 6MP-induced toxicities, but additional independent validations with large sample size and investigations on related mechanisms are further needed.